Experiments on Compound Risk in Relation to Simple Risk and to Ambiguity - Abdellaoui, Mohammed; Klibanoff, Peter; Placido, Lætitia (Management Science, 2015)
We conduct experiments measuring individual behavior under compound risk, simple risk, and ambiguity. We focus on (1) treatment of compound risks relative to simple risks and (2) the relationship between compound risk attitudes and ambiguity attitudes. We find that compound risks are valued differently than corresponding reduced simple risks. These differences measure compound risk attitudes. These attitudes display more aversion as the reduced probability of the winning event increases. Like Halevy [Halevy Y (2007) Ellsberg revisited: An experimental study. Econometrica 75:503–536], we find an association between compound risk reduction and ambiguity neutrality. However, in contrast to the almost perfect identification in Halevy’s data, we find a substantially weaker relation in both directions. First, a majority of our ambiguity-neutral subjects fail to reduce compound risk. Second, almost a quarter of our subjects who reduce compound risk are nonneutral to ambiguity. All of the latter come from the more quantitatively sophisticated part of our subject pool. Data, as supplemental material, are available at http://dx.doi.org/10.1287/mnsc.2014.1953 . This paper was accepted by Peter Wakker, decision analysis.